2018
DOI: 10.2320/matertrans.m2018208
|View full text |Cite
|
Sign up to set email alerts
|

Inoculant Fading-Resistance of Fe-Bearing Mg–3%Al Alloys Refined by Carbon Combining with Calcium Addition

Abstract: Mg3%Al alloys containing different trace Fe contents were treated by carbon combining with Ca inoculation. The holding time after being inoculation was adjusted from 5 to 80 min. The effect of holding time on grain refinement and the structures of nucleating particles were systematically investigated. Significant grain refinement is obtained for the Mg3%Al alloys containing trace Fe refined by carbon combining with Ca inoculation. The grain size keep stable with prolonging the holding time and exhibit signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 44 publications
1
5
0
Order By: Relevance
“…These results indicate that the trend of forming stable duplex-phase particles becomes more and more obvious during the carbon inoculation process. This result is also confirmed by our previous research, which showed that the duplex phase particles kept stable when prolonging the holding time to 80 min and exhibit significant fading resistance [6].…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…These results indicate that the trend of forming stable duplex-phase particles becomes more and more obvious during the carbon inoculation process. This result is also confirmed by our previous research, which showed that the duplex phase particles kept stable when prolonging the holding time to 80 min and exhibit significant fading resistance [6].…”
Section: Discussionsupporting
confidence: 89%
“…To exactly control the Al content in the Mg–Al melt, the amounts of Al in the pellets and the Al-15%Fe master alloy were carefully taken into consideration. The melting process used in this study is similar to that in our previous research [6]. The added contents of Fe, carbon, and Ca were 0.05%, 0.2%, and 0.2% (mass ratio, the same below) of the melt, respectively.…”
Section: Methodsmentioning
confidence: 70%
See 3 more Smart Citations